A human-body thermoelectric energy scavenging microsystem - Gonçalves, L. M. (2008)
A thermoelectric energy scavenging microsystem is proposed, optimized to convert the small thermal power available in human-body applications. A Lithium solid-state thin-film battery is integrated in the same device as well as the ultra low-power electronics to charge battery and perform DC-DC conversion.